Transformation toward precision large-scale operations for sustainable farming: A review based on China’s pig industry (Journal of Advanced Veterinary and Animal Research, 2024)
This review evaluates the current situation of pig farming, identifies challenges, and projects for the sustainable development of the Chinese pig industry. A literature review using keyword searches was conducted on Google Scholar for articles from 2017–2023. The review included studies focused on pig farming in China, covering prospects, challenges, quantitative data on production, marketing, and consumption, automation in livestock farming, and publications from peer-reviewed journals, credible websites, government reports, and conference proceedings. Pork consumption in China is increasing, and the country imports a sizable amount of pork annually. Even though small-scale farms still account for most operations, the pig industry is undergoing a critical stage of modernization and transition towards large-scale farming. The major challenges identified were feed, disease, antimicrobial resistance, environmental pollution, and pork prices. Smart technologies, such as cameras, Internet of Things, and sensors, integrated into precision pig farming can improve productivity and animal health through real-time data collection and decision-making. To solve the problems we face now, we need to put a lot of money into large-scale transformation, the creation of new animal precision tools, the automation of manure treatment, and the research and development of long-lasting alternative energy sources like photovoltaics and wind. By implementing these strategies, large-scale precision pig farming in China can become economically and environmentally sustainable, which can ultimately benefit consumers by supplying wholesome pork products.J. Adv. Vet. Anim. Res., 11(4): 1076–1092, December 2024http://doi.org/10.5455/javar.2024.k859